IMPLIKASI BELANJA DAERAH MENURUT FUNGSI TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI KALIMANTAN BARAT - B2053151007, DEWI ANGGRAINI (Jurnal Ekonomi Daerah (JEDA), 2017)
This study aimed to test: 1) the influence of the regional spending of ​​the economic functions of the HDI, 2) the impact of regional spending function fasum to HDI, 3) the influence of regional spending healthy functioning of the HDI, 4) the effect of regional spending educational functions of the HDI and 5) the impact of  regional spending social function area of ​​the HDI. This research uses a combination of data between the data time series with a cross Section. The sample used in this study as many as 14 districts / cities in 2010 to 2014. Selection of the research methods used by explanatory research method. The analysis used is multiple regression and t test statistic. The results showed regional spending the economic functions of, public facilities, health, education and social significant effect on the HDI simultaneously expressed in the coefficient of determination (R2) of 83.03%, which can be explained by the economic functions of regional spending, public facilities, health, education and social while the remaining 16.97% influenced by other variables. Research partially regional spending of public functions, education and social services Significant influence on the HDI, while spending on health and economic function area not significant effect on the HDI.   Keyword: regional spending, IPM